PENGARUH GAYA KEPEMIMPINAN, LOYALITAS KARYAWAN, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI LORIN SOLO HOTEL - Doni Mardiyanto; Mia Nur Handayani (ITB AAS Indonesia Surakarta, 2024)
This study aims to identify the influence of leadership style, employee loyalty, and communication on employee performance in a hotel company. This research employed a quantitative descriptive method. The data were collected uses sampling technique by distributing questionnaires to respondents. The population of this research was 76 employees of the Lorin Solo Hotel. This study applies the classical assumption test, multiple linear regression analysis, coefficient of determination (R2) test, t-test and F-test. The results of the analysis show that the leadership style variable has a value of fcount (4.799)>ftable (1.666), the employee loyalty variable has a value of fcount (5,187)>ftable (1,666), the communication variable has a value of fcount (3,614)>ftable (1,666). As a conclusion, the leadership style, the loyalty of the employees and the communication have a positive influence on the performance of the employees. Keywords: Leadership Style, Employee Loyalty, Communication, Employee Performance